Assessments of the effects of various fracture surface morphology on single fracture flow: A review - Min Gao; Chengguo Zhang; Joung Oh (International Journal of Mining Science and Technology, 2023)
Natural rock joint permeability deviates from the classic fluid flow governing equations due to the inherent fracture surface roughness (i.e., contact points, spatial correlation, matching, varying aperture, isolated voids, infilling material, tortuosity and channellings) and engineering disturbance such as excavations. To improve the accuracy of fracture permeability evaluation, many efforts have been made in analytical, experimental, and numerical methods. This study reviews the modified mathematical governing equations of fluid flow and classifies them based on different influencing factors, such as friction factor, aperture, tortuosity, inertia, and various in situ stress effects. Various experimental and simulation techniques for the coupled normal- and shear- stress flow problems were assessed, and their advantages and disadvantages were also analysed. Furthermore, different surface roughness descriptions and their impacts on mechanical and hydraulic behaviours were discussed, followed by the potential research directions for fracture flow problems.